PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA PADA MATERI DIMENSI TIGA BERBASIS APLIKASI ANDROID - Takdir, Muhammad (Universitas Negeri Makassar, 2018)
This study aims to determine the process and the development of mathematics learning media on three dimensional materials based on valid and practical, effective android applications. This research is a development of mathematics learning media on three dimensional material. The trial is limited to teachers and students intended to obtain a response, feedback on the learning media that has been developed. The results show that (1) The result of teacher response get the average score of 3.63 with very high category, (2) The result of the student response get the average score of 3.14 with high category, (3) classical reached 82.86%, (4) Results of students' motivation scores get 3.39 with high category. So based on the criteria, the learning media on the three dimensional materials based on android applications that have been developed declared valid, practical, and effective.